2015
DOI: 10.3151/jact.13.438
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Degradation of Concrete Anchorage Performance by Liquid Water

Abstract: Sludge ejection from the foundation of a wind turbine tower fixed by the anchor-ring method and the resulting sludge buildup have been confirmed to cause the undesirable phenomenon of lifting of the tower. Using specimen that is a partial model of the wind turbine foundation, this study investigates the influence of liquid water, differences in W/C, and differences in loading speed, to analyze developing factors on the concrete damage . The results shows that penetration of liquid water from rainfall and snowf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…This phenomenon has also been observed in wheel running tests for RC slabs where water is supplied to the upper surface [1]. Correspondingly, during the cyclic pull-out test of anchor frames, the pumping out of sludge from anchorage concrete was visible when water was supplied to the specimen [2]. In addition, the degradation of the rough cracked surface under the cyclic shear was clear when water was supplied to concrete specimens [3].…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…This phenomenon has also been observed in wheel running tests for RC slabs where water is supplied to the upper surface [1]. Correspondingly, during the cyclic pull-out test of anchor frames, the pumping out of sludge from anchorage concrete was visible when water was supplied to the specimen [2]. In addition, the degradation of the rough cracked surface under the cyclic shear was clear when water was supplied to concrete specimens [3].…”
Section: Introductionsupporting
confidence: 52%
“…For a further understanding of the phenomena, a multiple regression analysis for both the positive and negative water pressures was performed. = 0.0023 × ( ) − 0.0365 × ( ) + 0.1931 (2) where F is the weight of the fine aggregates, j(p) and j(n) are the degradation indices, focusing on the positive and negative water pressures, respectively. The coefficient of positive pressure (0.0023) was smaller than that of negative pressure (0.0365).…”
Section: Discussionmentioning
confidence: 99%
“…Although the authors have found no research into the effect of high water pressure on reinforcement bonding under static and cyclic conditions, they attributed that it influences the deterioration of the anchorage at the matrix/rebar interface. On the other hand, there have been a few studies on the fatigue response of reinforced concrete in the presence of water, which focused on the bond strength of deformed steel bars [ 36 , 37 , 38 , 39 ]. It was concluded that repeated reverse-cyclic loading led to pulverization of the concrete in the vicinity of the deformed steel bar, turning it into sludge and leading to pullout failure.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the structures supporting wind turbines, especially the foundation made of concrete, have been paid attentions in recent years. There are the reports that investigate cracks on foundation concrete [4][5][6][7]. It is not easy to identify the cause of cracks, while repeated action transferred from the tower is thought to be one of the causes.…”
Section: Introductionmentioning
confidence: 99%
“…It is not easy to identify the cause of cracks, while repeated action transferred from the tower is thought to be one of the causes. Therefore, fatigue of supporting structure made of concrete has become a main concern of researchers [7][8][9][10]. Even though the cracks are not always the trigger of structural collapse of wind turbine, further investigations are required for safe and steady operation of power plant.…”
Section: Introductionmentioning
confidence: 99%